Morphometric analysis of the intestine of domestic quails (Coturnix coturnix japonica) treated with different levels of dietary calcium - Aptekmann, K. P.; Artoni, SMB; Stefanini, M. A.; Orsi, M. A. (Blackwell Verlag Gmbh, 2001)
The aim of this study was to perform a morphometric analysis of the various parts of the intestine of the domestic quail. Twenty-four female quails (Coturnix coturnix japonica) aged 37 weeks were used and accommodated in laying cages for 12 weeks. Each group was fed a standardized diet containing different quantities of calcium: 2.0%, 2.5%. 3.0% and 3.5%. The birds were weighed, killed, and samples of 1 cm were collected from the duodenum, jejunum and ileum and submitted to the histological routine. The sections obtained were stained in haematoxylin & eosin (H&E). For morphometric analysis, 30 villi and 30 crypts of each segment of the small intestine were measured in order to determine the height and area of the villi, as well as the depth of the crypts. The results showed that although the integrity of the gastrointestinal tract was maintained in all the birds treated with the different calcium levels, a calcium level of 3.0% showed the most promise, as the levels of 2.0% and 2.5% did not cause any alteration in the intestinal tract. Furthermore, a calcium level of 3.5% led to a significant reduction in the height of the villosities, and in consequence reduced the digestive and absorptive capabilities.